How Toxic Workplace Environmet Effects the Employee Engagement and Employee Loyalty in Organization (Literature Review) - Andi Muhammad (Journal of Economics, Management, Entrepreneurship, and Business (JEMEB), 2023)
The purpose of this scientific article is to show that toxic environments are related to  employee  engagement and employee loyalty. The existing problems are based on existing literature reviews and are later presented from scientific articles. The results of the research are depicted at all of the three variables above that are directly used in one research or    scientific article with the results or objects of research from various journals that exist and are available. The conclusion of this scientific article illustrates that the literature review above reinforces the variables used by the author in writing this scientific article, thus adding to the characteristics of scientific results in   the field of human resources in general.    In the future this scientific article can be used or continued by other researchers for the development or production of research results that are expected with research objects that can adjust.